THE FUTURE OF MARKETING: EMERGING TRENDS AND TECHNOLOGIES - Dr. S.A.N.Shazuli Ibrahim, (EPRA International Journal of Research and Development (IJRD), 2023)
The field of marketing is constantly evolving, driven by advancements in technology and shifting consumer behaviors. The future of marketing by examining emerging trends and technologies that are reshaping the marketing landscape. It provides an overview of key developments and their potential impact on marketing strategies and consumer engagement. The importance of adapting to these changes and offers insights and recommendations for marketers to stay ahead in the dynamic and digitally-driven marketplace. The objective of this research study is to investigate the strategies and practices employed by successful organizations in anticipating and adapting to industry changes, particularly in relation to emerging trends and technologies to provide valuable insights into the proactive measures taken by organizations to stay ahead of the competition and effectively leverage emerging trends for sustained success in the dynamic marketing landscape. The diverse range of studies that contribute to our understanding of the future of marketing in the context of emerging trends and technologies. It emphasizes the significance of data-driven marketing, personalization, influencer marketing, voice search, and ethical considerations in shaping the marketing landscape. By building upon the existing body of knowledge, the research article on the future of marketing aims to provide further insights and practical recommendations for marketers to navigate and excel in this dynamic and evolving field.